EXPLORING THE ROLE OF STEM CELLS IN CANCER THERAPY - Swaha Bhattacharya; Sandeep Poddar, (The Malaysian Journal of Nursing (MJN), 2011)
The conventional methods for cancer treatment used so far are radiotherapy and chemotherapy. But, the drawbacks of these procedures are that most chemotherapy drugs and radiation techniques target the normally growing healthy cells of the body. They target the normal tissue as well, while being unable to completely destroy the cancer stem cells which are highly resistant to these technique. Solid tumors such as breast cancer and colon cancer possess a minor population of tumorigenic cells termed cancer stem cells (CSCs) or tumor initiating cells (TICs). A recent approach to deal with these problems is by making use stem cells. Stem cells are generally defined by an ability to differentiate into multiple cell lineages and self-renew. These stem cells have a number of utilities. They contribute to not only organogenesis but also help in regeneration in response to the injury of tissues and organs. Several studies conducted in the biology of stem cells have allowed for their identification and characterization in a variety of tissues and organs. This review makes an attempt to explore the behaviour and potential of stem cells in cancer treatment alongside the traditional methods of chemotherapy, radiation therapy and surgical removal of tumour.